Funding Decisions, Investment Decisions, Stock Prices, Dividend Policies, And Company Size’s Roles On Company Value - Hasanah, Sirotil; Wijaya, Ronni Andri; Sari, Desi Permata (GOVERNORS, 2024)
This study aims to determine the influence of funding decisions, investment decisions, stock prices, dividend policies, and company size on company value in companies in the consumer non-cyclicals sector for the 2019-2023 period. The population used in this study was 129 companies in the consumer non-cyclicals sector. The sampling technique used was a purposive sampling technique and was obtained by 31 companies in the consumer non-cyclicals sector as samples. The data in this study is secondary data in the form of annual data obtained from the official website of the Indonesia Stock Exchange. The data analysis technique used in this study is panel data regression analysis with the help of the Eviews 12 program. Based on the results of the tests carried out, it shows that the decision to invest in a relative has a significant effect on the value of the company, the investment decision in a relative has a significant effect on the value of the company, the stock price in a relative has a significant effect on the company's value, the dividend policy in a relative has a significant effect on the company's value, the size of the company in a significant effect on the company's value, funding decisions,  Investment decisions, stock prices, dividend policies, and company size simultaneously have a significant effect on the value of a company.